2007
DOI: 10.1152/ajpcell.00209.2006
|View full text |Cite
|
Sign up to set email alerts
|

EGF and HB-EGF modulate inward potassium current in human bladder urothelial cells from normal and interstitial cystitis patients

Abstract: TC. EGF and HB-EGF modulate inward potassium current in human bladder urothelial cells from normal and interstitial cystitis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…However, co-application of genistein with bpV(Phen) in differentiated myoblasts expressing Kir2.1 channels reduces the bpV(Phen)-induced Kir2.1 inhibition. Recently, it has been shown that a genistein pretreatment blocks the EGF-induced inhibition of Kir2.1 channels in urothelial cells (Sun et al, 2007). This observation supports the hypothesis that Kir2.1 channels activity can be directly modulated by a tyrosine phosphorylation.…”
Section: Kir21 Current Is Directly Modulated By the Tyrosine 242 Phosupporting
confidence: 72%
“…However, co-application of genistein with bpV(Phen) in differentiated myoblasts expressing Kir2.1 channels reduces the bpV(Phen)-induced Kir2.1 inhibition. Recently, it has been shown that a genistein pretreatment blocks the EGF-induced inhibition of Kir2.1 channels in urothelial cells (Sun et al, 2007). This observation supports the hypothesis that Kir2.1 channels activity can be directly modulated by a tyrosine phosphorylation.…”
Section: Kir21 Current Is Directly Modulated By the Tyrosine 242 Phosupporting
confidence: 72%
“…More recently, Sun and coworkers (33) discovered a channel in cultured human bladder epithelial cells with a strong inward-rectifying potassium current and conductance characteristics of the K ir 2.1 potassium channel. They also corroborated the presence of both K ir 2.1 and a large-conductance calcium-activated potassium channel (BK, or Maxi-K) presence in cultured human urothelial cells by RT-PCR and Western blot analysis (33). The cellular location of these channels was not reported.…”
supporting
confidence: 52%
“…Although the mechanism(s) of potassium reabsorption may, in part, be secondary to passive diffusion and or leak across the apical cell membrane or through tight junctions, in recent electrophysiological studies, Sun and coworkers (33) showed a strongly rectifying potassium current with conductive characteristics of the K ir 2.1 channel as well as the Maxi-K channel in normal cultured human bladder cells (33), and, in Ussing chamber experiments with rabbit bladder, Wang et al (35) demonstrated that increased mucosal hydraulic pressure led to increased sodium reabsorption (probably through ENaC) as well as potassium secretion, likely through a stretch-activated nonselective cation channel. Although none of these channels had the characteristics of ROMK channels, these findings support the hypothesis that multiple potassium channels and transporters are present in urothelia as is the case for renal epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, the author postulates that these diseases share ''dysfunctional urinary epithelium and potassium recycling'' impairment (30). Furthermore, all these diseases have been reported to respond to phytoestrogens, such as sitosterols, quercetin, and genistein (31)(32)(33). Many phytoestrogens, like genistein, are better ligands for ER␤ than ER␣ (34,35).…”
Section: Discussionmentioning
confidence: 99%